Bioaccumulation of Potentially Toxic Elements in Lettuce and Soil Fertility Treated with Biosolid - Gonçalves, Paula Wellen Barbosa [UNESP]; da Costa, Cândido Alves; Cardoso, Paulo Henrique Silveira; Pegoraro, Rodinei Facco; Cardoso, Gilmar Rodrigues; Versiani, Luis César Freire (Springer Nature, 2022)
The use of biosolids in agriculture contributes to soil fertility and plant nutrition. However, the presence of potentially toxic elements (PTEs) can limit its use as a fertilizer. In this context, we propose to evaluate PTEs bioaccumulation in lettuce and soil fertility treated with biosolid. The experiment was conducted in a completely randomized design with five replications. The treatments consisted of five doses of biosolids (0, 20, 40, 60, and 80 t ha−1) in an Oxisol. The fresh and dry matter of the aerial part and root of lettuce, PTEs concentration in the leaves of lettuce, and the soil chemical fertility after the application of the biosolid were determined. The biosolid application increased soil fertility, enhance soil pH, cation exchange capacity, and organic carbon concentration, providing greater production of lettuce fresh matter (121 g per plant at a dose of 67 t ha−1). With the increment of biosolid doses, a reduction in the concentration of As, Cr, Cu, Ni, Se, and Zn in lettuce leaves was observed. There was a negative correlation between the PTEs concentration in the plants and the soil attributes, which represents a reduction in the PTEs bioavailability as biosolid dose increases. However, the levels of Cd and Pb were above the limit established by Brazilian resolution for consumption, with or without biosolid application, indicating a high natural concentration of these elements in the soil. Biosolid increased soil fertility and lettuce production and decreased PTEs concentration in the leaves of lettuce.
Keywords: Composting; Heavy metals; Lactuca sativa L; Sewage sludge